Roles of Myeloid-Derived Suppressor Cell Subpopulations in Autoimmune Arthritis - Li, Min; Zhu, Dongwei; Wang, Tingting; Xia, Xueli; Tian, Jie; Wang, Shengjun (Frontiers in Immunology, 2018)
Emerging evidence suggests the promising prospects of myeloid-derived suppressor cells (MDSCs) in inflammatory disorders given the special immune intervention modalities demonstrated by these cells. However, the roles of MDSCs in autoimmune arthritis are not completely understood. In addition, their immunosuppressive functions in arthritis conditions remain controversial, and the MDSC heterogeneity and distinguished effects among MDSC subpopulations have received increased attention. As a result, it is necessary to determine the roles of MDSC subpopulations in autoimmune arthritis to clarify their diagnostic and therapeutic potential. Interestingly, both MDSC subpopulations exhibited two characteristics in inflamed niches of autoimmune arthritis. In addition, polymorphonuclear MDSCs (PMN-MDSCs) were likely to be more suppressive and stable compared with monocytic MDSCs (MO-MDSCs). Various important cytokines associated with the differentiation of MDSCs or MDSC subpopulations from immature myeloid precursors, such as granulocyte colony-stimulating factor (GM-CSF), have been largely applied in external inductive systems, but the roles of these cytokines still need to be further explored. As noted in other autoimmune diseases, MDSC-based clinical treatments in rheumatoid arthritis continue to represent a significant challenge. In this review, we describe the effects and actions of MDSC subpopulations on the development of autoimmune arthritis and analyze MDSC-based therapeutic strategies to provide comprehensive information regarding immune networks and to facilitate more effective protocols for rheumatoid arthritis (RA) treatments.